Size-resolved ambient bioaerosols concentration, antibiotic resistance, and community composition during autumn and winter seasons in Qatar - Bilal, Sajjad (2023)
This study investigates the size distribution, microbial composition, and antibiotic resistance (ABR) of airborne bioaerosols at a suburban location in Doha, Qatar between October 2021 and January 2022. Samples were collected using an Andersen six-stage viable cascade impactor and a liquid impinger. Findings showed that the mean bacteria concentration (464 CFU/m3) was significantly higher than that of fungi (242 CFU/m3) during the study period. Both bacteria and fungi were most abundant in the aerodynamic size fractions of 1.10–2.21 μm, with peak concentrations observed in the mornings and lowest concentrations in the afternoons across all size fractions. A total of 24 different culturable species were identified, with the most abundant ones being Pasteurella pneumotropica (9.71%), Pantoea spp. 1 (8.73%), and Proteus penneri (7.77%) spp. At the phylum level, the bacterial community configurations during the autumn and winter seasons were nearly identical as revealed by molecular genomics, with Proteobacteria being the most predominant, followed by Firmicutes, Bacteroidetes, Acidobacteriota, and Planctomycetota. However, there was a significant variation in dominant genera between autumn and winter. The most abundant genera included Sphingomonas, Paraburkholderia, Comamonas, Bacillus, and Lysinibacillus. Several bacterial genera identified in this study have important public health and ecological implications, including the risk of respiratory tract infections. Furthermore, the study found that ABR was highest in December, with bioaerosols exhibiting resistance to at least 5 out of 10 antibiotics, and 100% resistance to Metronidazole in all samples. Metagenomics analysis revealed the presence of various airborne bacteria that were not detected through culture-dependent methods. This study provides valuable insights into the airborne microbial composition, temporal variability and ABR in the Arabian Gulf region.